2013
DOI: 10.1188/13.onf.567-573
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship After Prostate Cancer Treatment: Spouses' Quality of Life at 36 Months

Abstract: Purpose/Objectives: To determine the long-term effects of prostate cancer treatment on spouse quality of life (QOL) at 36 months following treatment. Design: Descriptive-exploratory; community-based study. Setting: Telephone interviews. Sample: 95 female spouses of men treated for early-stage prostate cancer. Methods: A computer-assisted telephone interview was used to evaluate QOL among spouses of prostate cancer survivors at 36 months after initial prostate cancer treatment. Main Research Variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
1
36
0
2
Order By: Relevance
“…Potential changes in the quality of life might come forth in longitudinal studies of patients with prostate cancer and their spouses. Previous longitudinal studies have identified that spouses' quality of life is associated with their spouses' patient treatments for prostate cancer, especially if these patients report many side effects of their treatment (Green et al, ; Harden et al, ). Our findings show that patients experienced mildly higher physical functioning, emotional well‐being, and painlessness than spouses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential changes in the quality of life might come forth in longitudinal studies of patients with prostate cancer and their spouses. Previous longitudinal studies have identified that spouses' quality of life is associated with their spouses' patient treatments for prostate cancer, especially if these patients report many side effects of their treatment (Green et al, ; Harden et al, ). Our findings show that patients experienced mildly higher physical functioning, emotional well‐being, and painlessness than spouses.…”
Section: Discussionmentioning
confidence: 99%
“…The RAND‐36 is an internationally used instrument in measuring the HRQOL of patients with prostate cancer and their spouses (Cary et al, ; Dieperink et al, ; Harden et al, ; Treiyer, Anheuser, Butow, & Steffens, ; Vasarainen et al, ). In international surveys on patients with prostate cancer, the coefficients have been over 0.88 (Harden et al, , ). The reliability of the instrument has been tested in Finland, with Cronbach α coefficients for internal consistency at 0.80 to 0.94 (Aalto et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Another study about long-term effects of cancer treatment, performed on the wives of oncological patients, reported a similar level of distress and negative consequences of the diagnosis and intervention on intrafamilial interactions, changes in family roles and communication difficulties, just as in families without a history of cancer [11], families with a history of cancer who were able to act openly, to express feelings directly, to manage problems effectively, and to communicate information directly within the family, had lower levels of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Between 15% and 18% of patients report elevated depressive symptoms, and between 15% and 27% report elevated anxiety (e.g., Cliff & MacDonagh, 2000;Trinchieri, Nicola, Masini, & Mangiarotti, 2005). Spouse quality of life also declines, particularly among spouses reporting greater bother from the patient's urinary and sexual side effects (Harden, Sanda, Wei, & Northouse, 2013). Spouse depression and anxiety are also higher than the general population (e.g., Couper et al, 2006;Eton, Lepore, & Helgeson, 2005; Winters-Stone, Lyons, Bennett, & Beer, 2014)).…”
mentioning
confidence: 99%